A New Species of Clown Tree Frog, Dendropsophus leucophyllatus Species Group, from Amazonia (Anura, Hylidae) - Peloso, Pedro L. V.; Orrico, Victor G. D.; Haddad, Celio F. B. [UNESP]; Lima-Filho, Geraldo R.; Sturaro, Marcelo J. (Soc Brasileira Herpetologia, 2016)
We describe a new species of Dendropsophus (Anura: Hylidae: Hylinae: Dendropsophini) from the Amazon river (= Rio Amazonas) basin, state of Amazonas, northern Brazil. The new taxon is included in the D. leucophyllatus group based on its phylogenetic position and on the presence of a pair of pectoral glands (a likely synapomorphy of the group). The species is distinguished from other species in the group by its color pattern and the morphology of hand and feet tubercles. In order to assess the phylogenetic relationships of the new taxon, we compiled a dataset including mitochondrial and nuclear DNA sequence data for all but one species in the D. leucophyllatus group, plus a series of hylid outgroups. A tree-alignment (direct optimization) parsimony analysis firmly support the new species as the sister taxon of D. sarayacuensis. The monophyly of the D. leucophyllatus species group is not recovered in our analysis and the issue is discussed further.
Keywords: Amazon; Amphibia; Biodiversity; Hylinae; Phylogeny; Systematics; Taxonomy